2012
DOI: 10.1111/tpj.12008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolic profiling between desiccation‐sensitive and desiccation‐tolerant species of Selaginella reveals insights into the resurrection trait

Abstract: SUMMARYSpike mosses (Selaginellaceae) represent an ancient lineage of vascular plants in which some species have evolved desiccation tolerance (DT). A sister-group contrast to reveal the metabolic basis of DT was conducted between a desiccation-tolerant species, Selaginella lepidophylla, and a desiccation-sensitive species, Selaginella moellendorffii, at 100% relative water content (RWC) and 50% RWC using non-biased, global metabolomics profiling technology, based on GC/MS and UHLC/MS/MS 2 platforms. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 83 publications
(113 reference statements)
5
109
3
Order By: Relevance
“…Metabolome comparisons between these two grass species when both were fully hydrated, found higher concentrations of osmotically-active solute (osmoregulation and protection roles) and of nitrogen metabolites (retranslocation into young tissue and reserve roles) in Sporobolus stapfianus than in the sensitive species (Oliver et al 2011a). Similar observations have recently been reported for a sister group comparison between Selaginella lepidophylla and Selaginella moellendorffii (Yobi et al 2012).…”
Section: Phases In the Induction Of Desiccation Tolerancesupporting
confidence: 72%
See 2 more Smart Citations
“…Metabolome comparisons between these two grass species when both were fully hydrated, found higher concentrations of osmotically-active solute (osmoregulation and protection roles) and of nitrogen metabolites (retranslocation into young tissue and reserve roles) in Sporobolus stapfianus than in the sensitive species (Oliver et al 2011a). Similar observations have recently been reported for a sister group comparison between Selaginella lepidophylla and Selaginella moellendorffii (Yobi et al 2012).…”
Section: Phases In the Induction Of Desiccation Tolerancesupporting
confidence: 72%
“…(Iturriaga et al 2000). However, recent work has demonstrated that trehalose also accumulates to higher levels in the desiccation sensitive species Selaginella moellendorffii than it does in Selaginella lepidophylla under the same conditions (Yobi et al 2012). Thus it appears that trehalose accumulation is not necessarily required for desiccation tolerance and indeed in the same study it became clear that sucrose, as in other resurrection species, is the main protectant.…”
Section: The Molecular Biology Of Desiccation Tolerancementioning
confidence: 77%
See 1 more Smart Citation
“…For metabolite profiling, identification of known chemical entities was based on comparisons to metabolomic library entries of purified standards as previously described (33,34). Statistical analysis was performed using the software packages Array Studio (Omicsoft) and R (http://www .r-project.org/).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were analyzed on a Thermo Finnigan Trace DSQ fast-scanning single-quadrupole gas chromatograph-mass spectrometer using electron-impact ionization. For metabolite profiling, the identification of known chemical entities was based on comparison with metabolomic library entries of purified standards as described previously (Evans et al, 2009;Yobi et al, 2012).…”
Section: Extraction Of Exudate From Rootsmentioning
confidence: 99%